Investigation and design of microstrip patch antenna employed on PCs substrates in THz regime - Kushwaha, Ritesh Kumar; Karuppanan, P. (Australian journal of electrical & electronics engineering, 2021)
This article presents the application of photonic crystal (PCs) structures to design a microstrip patch antenna at terahertz (THz) frequency. An inset-feed rectangular microstrip antenna is proposed using 1D, 2D, 3D PCs substrate in 0.1-1 THz operating band. The spectral behaviour of 1D PCs exhibits the PCs' potential characteristics and demonstrates to use it in antenna design. The antenna radiation performance is performed using different PCs materials including air cavity (ɛ r = 1), polyamide (ɛ r = 3.5), paper (ɛ r = 2.5), FR4 (ɛ r = 4), Arlon (ɛ r = 2.2) and quartz (ɛ r = 3.78). It demonstrates that an air cavity photonic bandgap (PBG) type structure is more efficient than other PCs. Moreover, it reveals that 2D PCs-based antennas show a minimum reflection coefficient of −63.22 dB, maximum directivity of 6.81dBi, and radiation efficiency of 88.17% at 0.741 THz frequency. The antenna is a design and simulated by using CST microwave studio.